MANAJEMEN PENYELAMATAN IBU HAMIL PASCA BENCANA - Ika Nuria Syafira Iswarani; Ismatu Aghni Fatwa Izzati; Rusnaindah Ifta Firdausi; Dodik Nursanto (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2019)
Republic Indonesia is a disaster prone area, usually the victims are women, children, and elderly. The victim which need spesial treatment is pregnant women. The purpose of this literature review is to provide knowledge to readers in helping the post-disaster pregnant women. The method that we use in is reviewing articles through Google Scholar, Pubmed, and Mendeley. Before the evacuation, triage actions need to be carried out as an effort to sort out the patient's priorities based on the urgency of the management and consideration of the resources available for the management. Pregnant women are included in the first priority group (red) which means that they need immediate and appropriate help. The most appropriate evacuation for pregnant women is a sloping position with knees folded. If there is a back injury, make an effort so that the inferior vena cava is not crushed by the uterus. Injuries that need to be watched out for are bleeding, shock, DIC, and eclampsia. Nutritional and psychological recovery of pregnant women is also very important to prevent things that are not desirable for both mother and fetus.